Sirtuin 3 is essential for host defense against Mycobacterium abscessus infection through regulation of mitochondrial homeostasis. Issue 1 (31st December 2020) - Kim, Young Jae; Lee, Sang-Hee; Jeon, Sang Min; Silwal, Prashanta; Seo, Ju-Young; Hanh, Bui Thi Bich; Park, June-Woo; Whang, Jake; Lee, Min Joung; Heo, Jun Young; Kim, Soon Ha; Kim, Jin-Man; et al.
ABSTRACT: The global incidence of Mycobacterium abscessus (Mabc), a rapidly growing nontuberculous mycobacterial strain that causes treatment-refractory pulmonary diseases, is increasing. Despite this, the host factors that allow for protection against infection are largely unknown. In this study, we found that sirtuin 3 (SIRT3), a mitochondrial protein deacetylase, plays a critical role in host defense against Mabc infection. Mabc decreased SIRT3 and upregulated mitochondrial oxidative stress in macrophages. SIRT3 deficiency led to increased bacterial loads, histopathological, and mitochondrial damage, and pathological inflammation during Mabc infection. Administration of scavengers of mitochondrial reactive oxygen species significantly decreased the in vivo Mabc burden and excessive inflammation, and induced SIRT3 expression in infected lungs. Notably, SIRT3 agonist (resveratrol) significantly decreased Mabc growth and attenuated inflammation in mice and zebrafishes, indicating the key role for SIRT3 in metazoan host defense. Collectively, these data strongly suggest that SIRT3 is a host-directed therapeutic target against Mabc infection by controlling mitochondrial homeostasis.